2023
DOI: 10.3389/fpls.2023.1162572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different tillage systems and mowing time on nutrient accumulation and forage nutritive value of Cyperus esculentus

Abstract: Revealing the complex relationships between management practices, crop growth, forage nutritive value and soil quality will facilitate the development of more sustainable agricultural and livestock production systems. Cyperus esculentus is known as the king of oil crops and high-quality forage. However, there is little information about the effects of different planting modes {continuous cropping (CC)/rotation cropping (RC)} and initial mowing time on the plant nutrient accumulation and forage nutritive value.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Prior studies have established that promoting stolon tillering and shoot growth in tiger nut is essential for achieving high yields [ 8 ]. The investigations by DU et al [ 4 ] and Asare et al [ 5 ] revealed that for tiger nut plants to yield exceptionally high tuber yield, robust development of stolon tillering and shoots is necessary, which, in turn, facilitates the generation of a greater number of tubers within the crop population. This research highlights that the most effective N fertilizer treatment for maximizing yield primarily works by increasing the number of individual grains and stolon tillering, thereby leading to a high yield outcome ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have established that promoting stolon tillering and shoot growth in tiger nut is essential for achieving high yields [ 8 ]. The investigations by DU et al [ 4 ] and Asare et al [ 5 ] revealed that for tiger nut plants to yield exceptionally high tuber yield, robust development of stolon tillering and shoots is necessary, which, in turn, facilitates the generation of a greater number of tubers within the crop population. This research highlights that the most effective N fertilizer treatment for maximizing yield primarily works by increasing the number of individual grains and stolon tillering, thereby leading to a high yield outcome ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tiger nut ( Cyperus esculentus L.), known as chufa, is an underappreciated crop that is rich in nutrition and has been attracting increasing interest owing to the variety of beneficial substances in its tubers [ 1 , 2 ]. This product is transformed into cooking oil, flour, health supplements, and cosmetics to cater to a diverse range of human needs [ 3 , 4 , 5 , 6 ]. For instance, in Spain, it is utilized to manufacture beverages, whereas in Africa, it acts as an alternative to flour, addressing food insecurity [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%